Visions and Revisions: The Multiple Lives of Mina Loy’s Lunar Baedeker - Diane Drouin (Transatlantica)
The editors of Mina Loy’s four collections of poems—Lunar Baedecker (1923), Lunar Baedeker and Time-Tables (1958), The Last Lunar Baedeker (1982), and The Lost Lunar Baedeker (1996)—all opted for a range of titles based on the same lunar imagery. However, the teleological and linear perspective on Loy’s Lunar Baedeker, leading from the original volume of Lunar Baedecker to the variation of Lunar Baedeker and Time-Tables, then to a final “last” version and finally to an ultimate “lost” version, should be reconsidered. While each collection offers a valuable insight into Loy’s work, none amounts to a stable, definitive text. Rather, they should be regarded as different versions of Loy’s poetic vision. Multiple layers of text are thus displayed, characterized by constant alteration and instability. This article argues that the notions of vision and reframing can be metaphorically applied to the multiple versions of Loy’s Lunar Baedeker, first through her own constant revisions and rewritings of her work, and then through the editorial process and critical approaches that reframed her poems and their reception over the years. I suggest that, despite various editorial attempts at containing and fixing her poems within the scope of a final collection, her poetry books are elusive and constantly evolving. The analysis of the multiple forms of Loy’s Lunar Baedeker, from her manuscripts in the archives of the Mina Loy Papers to her printed collections, and to recent digital versions of her poems, allows for a fruitful reframing of her work.